Adipose-immune interactions in obesity - Dixit, Vishwa (Henry Stewart Talks, 2009)
Adipoimmunology, The adipose organ in obesity, The immune system, Adipose tissue macrophages and inflammation, Differentiation of macrophages, Effect of obesity on adipose tissue macrophages, Macrophages cause insulin resistance in obesity, ATM polarization model, Future directions: ATM and adipose tissue, Adipose tissue lymphocytes and inflammation, T-lymphocytes subsets, CD3+ T cells are present in the adipose tissue, Age related increased bone-marrow adipocity, Age related thymic adipocity, T cells develop in the thymus, The effect of thymic involution, Lineage of thymic adipocytes, Loss of ghrelin signaling and thymic adiposity, reduction in naive T cells, Adipose secretory products and immune cells, Effect of obesity on immune function, Obesity induced by monogenic leptin deficiency, Dietary obesity reduces lymphoid cellularity, Dietary obesity induces apoptosis of T cells, Influenza infection and diet-induced obese mice